2021
DOI: 10.1515/jbcpp-2020-0378
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cardiac autonomic function in COVID-19 using heart rate variability: a hospital based preliminary observational study

Abstract: Objectives The novel corona virus disease, which was initially reported in China in late 2019, has become a global pandemic affecting 330 million cases. COVID-19 affects predominantly the respiratory system, in addition to other organ systems, mainly the cardiovascular system. One of the hypotheses is that virus entering the target cells by binding to angiotensin converting enzyme 2 affecting hypothalamic pituitary axis could lead to dysautonomia which is measured by heart rate variability (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
118
2
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(126 citation statements)
references
References 43 publications
2
118
2
4
Order By: Relevance
“…There was no significant difference in terms of age, sex, and mean pulse rate between the two evaluated groups (P ¿0.05). In line with our results, a case-control study comparing the COVID-19 infected patients and healthy matched controls reported that vital parameters like heart rate, systolic, and diastolic blood pressure showed no difference between the study groups (15).…”
Section: General Characteristics and Clinical Presentationssupporting
confidence: 91%
See 1 more Smart Citation
“…There was no significant difference in terms of age, sex, and mean pulse rate between the two evaluated groups (P ¿0.05). In line with our results, a case-control study comparing the COVID-19 infected patients and healthy matched controls reported that vital parameters like heart rate, systolic, and diastolic blood pressure showed no difference between the study groups (15).…”
Section: General Characteristics and Clinical Presentationssupporting
confidence: 91%
“…COVID-19 predominantly affects the respiratory system. It shows a wide range of clinical presentations ranging from asymptomatic/mild symptoms (fever, cough, dyspnea, myalgia, fatigue, anosmia, dysgeusia, and diarrhea) to severe illnesses like acute respiratory distress syndrome (ARDS), arterial and venous thrombosis, myocarditis, and varieties of neurological manifestations (15). COVID-19 can cause shortness of breath, lung damage, and impaired respiratory function.…”
Section: General Characteristics and Clinical Presentationsmentioning
confidence: 99%
“…In addition to Tilt Table Testing, Valsalva maneuver, deep breathing test, isometric exercise test and heart rate variability, either in a dedicated laboratory or assessed with a 24-h Holter monitor with appropriate software are mainstays for assessment. Heart rate variability has also been determined in hospitalized patients with COVID-19 using an abbreviated 5-min protocol [ 85 ]. Measurement of plasma catecholamines may be useful (reviewed in Guaraldi) [ 86 ].…”
Section: Anatomy Of the Autonomic Nervous Systemmentioning
confidence: 99%
“…According to research, COVID‐19 has an effect on the autonomic nervous system; so that concepts such as the extended autonomous system (EAS), allostasis, and dyshomeostasis may reflect COVID‐19's age‐related mortality and the involvement of several organ sites in the disease 23 . One study found that COVID‐19 patients had increased parasympathetic activity and autonomic imbalance despite key factors such as age, gender, and comorbidities like diabetes mellitus 24 . COVID‐19 and the autonomic system have a complicated relationship.…”
Section: Introductionmentioning
confidence: 99%